2019
DOI: 10.3390/app9214588
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variability of Drought in Pakistan Using Standardized Precipitation Evapotranspiration Index

Abstract: Featured Application:The following research has a potential to provide a scientific basis for the management of drought mitigation strategies. The trends in drought characteristics in each zone throughout the study period can help decision-makers with more information on resource planning. The identification of contiguous zones with similar drought characteristics across Pakistan is the first step towards developing an integrated and holistic policy to minimize the impacts of droughts. This study will help ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 28 publications
6
38
1
Order By: Relevance
“…Therefore, in this study, we have used SPEI as the drought index and extended the study period to 1902-2015. This study also aims to extend the Pakistan-wide work of Jamro et al [26], which concluded that central Balochistan, along with Sindh, is the most vulnerable area to droughts and requires further investigation.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, in this study, we have used SPEI as the drought index and extended the study period to 1902-2015. This study also aims to extend the Pakistan-wide work of Jamro et al [26], which concluded that central Balochistan, along with Sindh, is the most vulnerable area to droughts and requires further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…Regionalization is a popular technique used in hydrology to group stations into clusters showcasing similar behavior when comparing a certain attribute. The regionalization of droughts has been carried out in this study using a Spatial "K"luster Analysis using Tree Edge Removal (SKATER) algorithm [18,26,38] to divide Balochistan into six regions having a similar behavior of SPEI. A 24-month SPEI was used to cluster the 124 grid cells in Balochistan into six spatially contiguous regions, as this timescale was found to reflect the climate of Balochistan better than other timescales of SPEI.…”
Section: Drought Regionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two types of drought arise when use of water resources exceeds renewal of surface and groundwater, or when water demand outstrips supply.Many drought indices have been developed to date, such as the Palmer drought severity index [26], decile index [27], standardized precipitation index (SPI) [28], streamflow drought index (SDI) [15], and standard contribution of rainfall to runoff (SCRI) [29]. Of these, SPI and SDI have been widely used in different climate zones to monitor and assess meteorological drought [30][31][32][33][34][35][36] and hydrological drought [37][38][39][40].Although there has been considerable progress in understanding the impacts of drought in terms of engineering, economics, social science, and geography, the complex links between human and natural processes need more attention. In arid and semi-arid regions with high dependency on agriculture, these links are more complicated, as they affect the livelihoods of local people.…”
mentioning
confidence: 99%
“…Many drought indices have been developed to date, such as the Palmer drought severity index [26], decile index [27], standardized precipitation index (SPI) [28], streamflow drought index (SDI) [15], and standard contribution of rainfall to runoff (SCRI) [29]. Of these, SPI and SDI have been widely used in different climate zones to monitor and assess meteorological drought [30][31][32][33][34][35][36] and hydrological drought [37][38][39][40].…”
mentioning
confidence: 99%